The Hamiltonean P-Median Problem - Branco, I. M. (1986)
The paper is concerned with a new mixed routing location problem embedding the p - median and the travelling salesman problems. The Hamiltonean p - median problem (HPMP) is formulated and several heuristics are proposed. Computacional experience with a set of test problems is reported.